Use of mobile devices in the promotion of health and well-being in young university students - Pera, Lidia Ysabel Pareja (2023)
Introduction: in the digital age we live in, mobile devices (DMs) have become a fundamental extension of our lives, and college students are no exception. Young university students are increasingly turning to their MD as multifunctional tools to address aspects related to their physical, emotional and social well-being. Objective: to characterize the use of DM in the promotion of health and well-being in young university students. Methods: the study is cross-sectional with a quantitative approach and a non-experimental design, basic type and descriptive level was adopted. The sample was census made up of 89 students from the Faculty of Health Sciences of a public university in Trujillo, Peru. To collect the data, the survey and the questionnaire were used. Results: regarding the use of DM, it was reported that 61,80 % (55) specified a moderate level of use, 21,35 % (19) a high level, and 16,85 % indicated a low level. Therefore, the use of DM motivates them to maintain an active and healthy lifestyle, which may be essential to maintain a constant exercise routine. Conclusions: it was possible to specify a moderate level in the use of DM, which suggests that they find a balance between the use of DM for activities such as monitoring physical activity, stress management, access to health information and participation in online communities related to health and wellness.